Unilateral contract, as the basis of occurrence property rights to another’s real estate - Maika, Nataliia; Yatsishin, O. (Actual problems of law (Aktual’ni problemi pravoznavstva), 2019)
In article is considered the legal nature of unilateral contracts, which have no contractual nature and which mediate the establishment of real rights to someone else’s real estate. On the basis of the analysis of blighty legislation and scientific doctrine, is formed types of these unilateral contracts. Most legal actions of real legal relations are legal acts. However, in science of civil law is not enough attention to unilateral contract as the basis of occurrence property rights to another’s real estate. The subject of our study is the legal act, which do not have contractual nature. We talk about unilateral contract as the basis of occurrence property rights to another’s real estate in order inheritance (testament, testamentary disposition, testamentary refusal). Unilateral contract as the basis of occurrence property rights to another’s real estate is legitimate, volitional action by person and directed to occurrence property rights to another’s real estate. This legal action commit by person which has the proper authority. Basis of occurrence property rights to another’s real estate is unilateral contract which combine unilateral authorization and unilateral obligation. The will by the legal nature is unilateral contract with expression of will one person (exception the will of the spouses). Order of the testator can be occurrence property rights to another’s real estate. That is to give a third person property rights to another’s real estate. The testamentary refusal is order of the testator within the will which is aimed at establishing a singular succession. However, the testamentary refusal is not recognized directly by law as the basis of occurrence property rights to another’s real estate. Summarizing the foregoing, one can conclude that the grounds for the real rights to someone else’s real estate are unilateral acts combining unilateral authorizations and unilateral commitments. It is about the establishment of such rights in the order of inheritance (will, testamentary order, performed by the testator in the will, and also based on a willful denial). Unilateral transaction as the basis for the establishment of real rights to someone else’s real estate - is a legitimate, voluntary action of a person, aimed at acquiring a real right to someone else’s property, committed by a person who has the appropriate powers in relation to the thing and aims to consciously create specific civil-law consequences for themselves or other people.